Cellular lensing and near infrared fluorescent nanosensor arrays to enable chemical efflux cytometry - Soo-Yeon Cho (Nature Portfolio, 2021)
The authors present nanosensor chemical cytometry, based on an array of nIR fluorescent single walled carbon nanotube integrated along a microfluidic channel. The lensing effect of the flowing cells allows for extracting information, and correlating biomolecular information with physical properties.